Conditional cash transfers in OECD countries: a realist synthesis - Mazzeo Rinaldi, Francesco; Leone, Liliana (Frontiers in Sociology, 2023)
Conditional Cash Transfers (CCTs) schemes have been adopted mostly in low-income countries as a tool to break the vicious cycle of poverty transmission. Although their use is controversial, behavioral conditionalities have also been widely used in welfare-to-work strategies, minimum income scheme, and labor market "activation" policies in OECD countries. The paper presents the results of a Realist Review to synthesize the evidence of CCTs related to work conditionality, delivered in OECD countries. The evaluation literature of 23 selected CCTs programs was analyzed by reconstructing Context-Mechanism-Outcome configurations. The main findings show that CCTs can be an effective counterbalance to work disincentives introduced by welfare measures. The unintended negative impacts, the role of sanctioning, and the causal pathways that may affect the most disadvantaged people and their children are discussed.